Fiqh Daily Prison: Practical Solutions of Islamic Law for the Problems of Prisoners - Najamuddin Najamuddin; Ridhoul Wahidi; Riki Rahman (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
The article aimed to answer the daily fiqh problems of prisoners in Correctional Institutions (Lapas) class II Tembilahan. The fiqh problems related to Islamic law relating to individuals, relationships with God and prison society. The structured interviews with prisoners and the study of relevant documents were used to answer the research questions. This research uses a qualitative approach and literature by referring to classical and contemporary fiqh books. This research resulted in the findings of the formulation of daily fiqh of prisoners in Class II Tembilahan Correctional Institution, namely: First, related to fiqh laws that concern individual issues such as masturbation, tattoos, vital organs installed with roles to becoming prayer leader (imam), paying debts from drug money, anxious between farting or not at the time of bowing or prostration, the law of not providing maintenance for the wife for a long time, and apologizing to parents who have died. Secondly, there is the issue of fiqh rulings between the servant and Allah. In this case, one issue is the law of the zuhur prayer being performed before the Friday prayer. Third, issues related to relationships with society. In this case, there is one issue, namely maintaining tolerance for non-Muslims in prison. This research contributes to providing Islamic legal solutions to the daily problems of Muslim prisoners to continue to carry out religious obligations in correctional institutions and as a reference for policymakers in correctional institutions to continue to present legal benefits for Muslim prisoners.